A Genomic-Systems Biology Map for Cardiovascular Function - Stoll, Monika; Cowley, Allen W.; Tonellato, Peter J.; Greene, Andrew S.; Kaldunski, Mary L.; Roman, Richard J.; Dumas, Pierre; Schork, Nicholas J.; Wang, Zhitao; Jacob, Howard J. (Science (American Association for the Advancement of Science), 2001)
With the draft sequence of the human genome available, there is a need to better define gene function in the context of systems biology. We studied 239 cardiovascular and renal phenotypes in 113 male rats derived from an F2intercross and mapped 81 of these traits onto the genome. Aggregates of traits were identified on chromosomes 1, 2, 7, and 18. Systems biology was assessed by examining patterns of correlations ("physiological profiles") that can be used for gene hunting, mechanism-based physiological studies, and, with comparative genomics, translating these data to the human genome.